On the desirability of the West African monetary union - (:unkn) unknown (My University, 2021)
In this paper, we investigate from a policy coordination viewpoint the desirability of the West African monetary union project, ECO. Our approach is built around the inclusion of national objectives in the regional integration perspective. Thanks to cluster analysis, we identify two groups of countries with relatively homogenous sustainable exchange rate paths in West Africa. We also find that no single currency peg nor a freely floating exchange rate regime would be preferable for any of the countries or groups of economies. Overall, our findings argue in favor of two ECOs —at least in a first step, i.e., one for each of the two identified zones. Each ECO would serve as a virtual anchor —with some flexibility— for the considered group, and would be determined by a basket of currencies mainly composed of euro and US dollar.
Keywords: African Research